Determinan Tax Avoidance - Sri Ayem; Elis Apriliani (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of financial disress, fixed asset intensity and accounting conservatism on tax avoidance. This research includes quantitative research. The population in this study are trading companies lited on the Indonesia Stock Exchange in 2020-2021. The sample in this study was determined by purposive sampling method and the data obtained were 40 companies, the sample within 2 years of annual financial reposts. The data analysis technique used includes multiple regression and the type of data used is secondary data. The results of this study indicate that fixed asset intensity has a positive effect on tax avoidance, financial distress and accounting conservatism have no effect on tax avoidance.